2018
DOI: 10.1039/c8nr01421c
|View full text |Cite
|
Sign up to set email alerts
|

π–π stacking induced high current density and improved efficiency in ternary organic solar cells

Abstract: Ternary blend systems have been used to enhance the short-circuit current density (JSC) and fill factor (FF) of organic solar cells (OSCs). However, it is still a challenge to find suitable third components that concurrently possess complementary light absorption and well-matched energy levels. Here, a small organic molecule, 4,4'-(9,9-dihexyl-9H-fluorene-2,7-diyl)bis(N,N-bis(4-(pyren-1-yl)phenyl)anili-ne) (DFNPy), which contains a triphenylamine core and bulky pyrene rings, was designed and used to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…In Figure 7, it is found that the WCA value is 99.44° of PTB7-Th:PC 70 BM, which is close to the pure film of PTB7-Th (103.28°), indicating that more PTB7-Th gather on the blend film superficially, in addition to the small amount of PC 70 BM molecules. [28,44] The miscibility between the different components is recognized as the key factor in determining the vertical and horizontal phase separation, and eventually the performance of solar cells. The WCA values are 102.04° of ternary films containing 10 wt% DRCN5T and 103.22° of ternary films containing 30 wt% DRCN5T, which are very close to the pure PTB7-Th film of 103.28°.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 7, it is found that the WCA value is 99.44° of PTB7-Th:PC 70 BM, which is close to the pure film of PTB7-Th (103.28°), indicating that more PTB7-Th gather on the blend film superficially, in addition to the small amount of PC 70 BM molecules. [28,44] The miscibility between the different components is recognized as the key factor in determining the vertical and horizontal phase separation, and eventually the performance of solar cells. The WCA values are 102.04° of ternary films containing 10 wt% DRCN5T and 103.22° of ternary films containing 30 wt% DRCN5T, which are very close to the pure PTB7-Th film of 103.28°.…”
Section: Resultsmentioning
confidence: 99%
“…[42] There are multiple reasons for the poor performance of ternary OSCs with thicker active layer. [21,44] Weather the substrate character is hydrophobic or not, it is still unknown that what determines the morphological stability of thick active layer in the vertical direction. [38] Furthermore, as the blend film thickness increased, the effect of surface energy of substrates on the vertical distribution of donor and acceptor lessened, leading to the unfavorable enrichment of donors or acceptors at cathode and anode, which is harmful to the charge collection in the respective electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S3 (Supporting Information) shows the hole mobility properties that were calculated by using the space charge limited current method. The hole mobility was estimated by using the Mott–Gurney equation and by fabricating a hole only device (ITO/active layer/MoO 3 /Ag or ITO/PEDOT:PSS/active layer/MoO 3 /Ag)J=9normal/8με0εnormalrV2normal/L3where µ : Charge carrier mobility,ε 0 : Free‐space permittivity, ε r : Dielectric constant of the semiconductor, V : Applied voltage, L : Thickness of semiconductor layer. …”
Section: Resultsmentioning
confidence: 99%
“…The photovoltaic performance of BHJ PSCs was highly dependent on the semiconductor materials used as the photoactive layer. Thus, tremendous efforts in the past decades have been devoted to exploring excellent semiconducting materials, such as conjugated copolymers (CPs) and small molecules (SMs), and the use of various additives to modulate the morphology and optimization of processing techniques [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Recently, with the help of novel materials, improved morphology, much more profound understanding of the structure-performance correlation and the photon-to-electron conversion mechanism, and power conversion efficiencies (PCEs) for PSCs in the single-junction module of over 11% in fullerene systems [35] and over 16% in non-fullerene systems [36][37][38][39] were achieved.…”
Section: Introductionmentioning
confidence: 99%